2016
DOI: 10.3892/etm.2016.3585
|View full text |Cite
|
Sign up to set email alerts
|

Molecular examination of bone marrow stromal cells and chondroitinase ABC-assisted acellular nerve allograft for peripheral nerve regeneration

Abstract: The present study aimed to evaluate the molecular mechanisms underlying combinatorial bone marrow stromal cell (BMSC) transplantation and chondroitinase ABC (Ch-ABC) therapy in a model of acellular nerve allograft (ANA) repair of the sciatic nerve gap in rats. Sprague Dawley rats (n=24) were used as nerve donors and Wistar rats (n=48) were randomly divided into the following groups: Group I, Dulbecco's modified Eagle's medium (DMEM) control group (ANA treated with DMEM only); Group II, Ch-ABC group (ANA treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…28 However, we found lower VEGF levels than those in the G-CSF or exercise groups, which differed from the results of a previous study. 29 we could explain our findings as G-CSF promotes angiogenesis first and stimulates neurogenesis later. Thus, neurogenesis was more critical than angiogenesis for motor function recovery, and combined treatment was more effective for motor function recovery because neurogenesis progressed faster than individual treatment.…”
Section: Discussionmentioning
confidence: 55%
“…28 However, we found lower VEGF levels than those in the G-CSF or exercise groups, which differed from the results of a previous study. 29 we could explain our findings as G-CSF promotes angiogenesis first and stimulates neurogenesis later. Thus, neurogenesis was more critical than angiogenesis for motor function recovery, and combined treatment was more effective for motor function recovery because neurogenesis progressed faster than individual treatment.…”
Section: Discussionmentioning
confidence: 55%
“…As the development of tissue engineering, the biodegradable artificial nerve is an alternative to autologous nerve grafts and used to bridge the stumps of defected peripheral nerve. Poly lactic co-glycolic acid (PLGA) nerve conduit can be combined with different donor cells, such as neural stem cells (NSCs; Omi et al, 2016 ), bone marrow stromal cells (BMSCs; Ying et al, 2016 ), shwann cells (SCs; You et al, 2011 ), olfactory ensheathing cells (OECs; Guerout et al, 2014 ), epidermal neural crest stem cells (EPI-NCSCs; Zhang et al, 2014 ), to provide a favorable microenvironment for preventing infiltration of scar tissue and guiding axonal regeneration (Li B. C. et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, BMSCs are preferred seed cells for use in constructing tissue‐engineered nerve transplants. An increasing number of in vivo studies have confirmed preferable therapeutic effects of BMSCs on neural regeneration (Wang et al, , Zarbakhsh, Goudarzi, Shirmohammadi, & Safari, ).…”
Section: Discussionmentioning
confidence: 98%
“…Bone marrow stromal cells (BMSCs) are attractive adult stem cells, since they possess merits such as easy accessibility, rapid proliferation, persistent survival and immunological compatibility; in addition, these cells are capable of undergoing multi‐directional differentiation and secreting of neurotrophic factors (Ide and Kanekiyo, ; Yang et al, ; Zheng et al, ). BMSCs have been utilized to repair central and peripheral neural injuries to some extent (Cuevas, Carceller, Garcia‐Gomez, Yan, & Dujovny, ; Hokari et al, ; Polisetti, Chaitanya, Babu, & Vemuganti, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%